1998
DOI: 10.1016/s0014-5793(98)00491-8
|View full text |Cite
|
Sign up to set email alerts
|

Indirect evidence for structural changes coupled with Q−⋅B formation in photosystem II

Abstract: The thermal blockage of 3c e oxidation was analysed in PS II membrane fragments by monitoring flash-induced changes of the relative fluorescence quantum yield as a function of temperature. The results obtained reveal: (a) in dark-adapted samples the fraction of 3c e that is not reoxidised within a time domain of 10 s after the actinic flash increases with lowering the temperature (half-maximum effect at 250^260 K), (b) at low temperatures where 3c e generated in dark-adapted samples remains almost completely r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(17 citation statements)
references
References 24 publications
1
16
0
Order By: Relevance
“…Interestingly, the transfer step from Q A -• to Q B -• is less affected by temperature decrease, as was found in experiments using samples frozen after preillumination with one saturating laser flash at room temperature (12). The stepwise oxidation of the WOC by the tyrosine Y Z OX is also sensitive † Financial support by Deutsche Forschungsgemeinschaft (SFB 429, TP A1) is gratefully acknowledged.…”
mentioning
confidence: 76%
“…Interestingly, the transfer step from Q A -• to Q B -• is less affected by temperature decrease, as was found in experiments using samples frozen after preillumination with one saturating laser flash at room temperature (12). The stepwise oxidation of the WOC by the tyrosine Y Z OX is also sensitive † Financial support by Deutsche Forschungsgemeinschaft (SFB 429, TP A1) is gratefully acknowledged.…”
mentioning
confidence: 76%
“…from its freezing-out at cryogenic temperatures (15,16,59,60) and from the driving force-independent kinetics (15)(16)(17)61). The gating concept explains why the experimentally accessible (monophasic) reaction kinetics are slower than predicted by ET theory (62).…”
Section: Discussionmentioning
confidence: 99%
“…The temperature, which enables 50% activity, is higher for ET to Q B than to Q À B in both spinach thylakoids and PSII membrane fragments Reifarth and Renger 1998). Mößbauer spectroscopy Photosynth Res (2007) 94: 183-202 189 studies using 57 Fe labeled NHFe as a probe (Garbers et al 1998) and measurements of quasielastic neutron scattering (QENS) (Kühn et al 2005, Pieper, Hauß, Buchsteiner, Baczyński, Adamiak, Lechner, Renger unpublished results) revealed that the threshold temperature for increased protein flexibility is virtually the same as for the onset of Q À A reoxidation by Q B .…”
Section: Kinetics and Energetics Of Pqh 2 Formationmentioning
confidence: 93%